Development of instrument in measuring family communication patterns and family well-being through the Islamic perspective - Mohamed Hussan, Khairunnisa (2021)
Communication in the family has been declared as a way to measure family satisfaction. Therefore, McLeod and Chaffee have developed a measurement to measure family communication patterns in 1972 and later was revised by Fitzpatrick and Ritchie in 1994. In addition, family well-being is important to the achievement of a better communities. Families that can make right decisions, fulfill their basic needs and address community challenges are better equipped to enjoy happier and healthier life. As a result, there were a lot of research on family communication patterns and family well-being that used the instrument constructed by the western scholars. However, the suitability of the instrument need to be re-evaluated so that the measurements used are accurate and relevant with the Islamic perspective. Therefore, this study aims to dig up what has been shown in Al-Quran and Hadith Prophet s.a.w. and transform it into indicators in developing an instrument that is based on the Islamic perspective. This study has employed an exploratory sequential mixed-methods. It has started with qualitative method via a document analysis and then continued to get depth understanding via an in-depth interview with the experts in Islamic field. Based on the findings from the in-depth interview, the first draft of the newly instrument has been produced which contains thirty items to measure family communication patterns and thirty items to measure family well-being. After that, it has been moved to the second phase where the newly developed instrument need to be tested quantitatively. Content validation has been done with five experts to check on the items measure what it should been measured. In the face validation, two experts has checked on the possibility of misinterpreted or misunderstood questions in the newly developed instrument. The newly developed instrument then has been distributed to one hundred and ten respondents in two phase. After each phase, exploratory factor analysis and confirmatory factor analysis have been conducted. Moreover, interclass correlation coefficient has been carried out in order to get the consistency of the result over time. As a result, the final version of the newly developed instrument has been produced which contains twenty seven items to measure family communication patterns and twenty one items to measure family well-being. In conclusion, this study has contributed to the development of an instrument that measures family communication patterns and family well-being in Islamic perspective that is suitable to be used by Muslim families in Malaysia. However, this study only be conducted until validation phase and future researchers are encourage to continually distribute this newly developed instrument to wider respondents of Muslim families in Malaysia.